2020
DOI: 10.20517/2347-9264.2020.150
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as an orchestrator of cutaneous scar formation: a review of the literature

Abstract: Inflammation is a key phase in the cutaneous wound repair process. The activation of inflammatory cells is critical for preventing infection in contaminated wounds and results in the release of an array of mediators, some of which stimulate the activity of keratinocytes, endothelial cells, and fibroblasts to aid in the repair process. However, there is an abundance of data suggesting that the strength of the inflammatory response early in the healing process correlates directly with the amount of scar tissue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 166 publications
(173 reference statements)
0
21
0
Order By: Relevance
“…An imbalanced or persistent inflammatory response is believed to contribute to scar formation and fibrosis [ 7 ]. One inflammatory cell type that has been proposed to drive fibroblast activation and excessive collagen deposition is the mast cell.…”
Section: Introductionmentioning
confidence: 99%
“…An imbalanced or persistent inflammatory response is believed to contribute to scar formation and fibrosis [ 7 ]. One inflammatory cell type that has been proposed to drive fibroblast activation and excessive collagen deposition is the mast cell.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive scarring and fibrosis have been linked to macrophage dysfunction in a wide range of injuries [ 61 ]. The topic of macrophages as critical mediators of scar formation has been widely studied and thoroughly reviewed recently [ 62 ]. In short, the balance between regeneration of tissue and scar-forming repair seems linked to macrophage function, with excessive inflammation leading to fibrotic rather than regenerative repair.…”
Section: Macrophages In Regenerative Speciesmentioning
confidence: 99%
“…Scarring is strikingly linked to inflammation; it is caused by immune cell interactions that produce several cytokines that activate mesenchymal cells and fibroblasts, promoting fibroplasia, contraction, and collagen production. According to the data, the strength of the inflammatory response correlates strongly with the amount of the scar that the tissue or organ will form, for more information review [137]. However, research in different regenerative models has shown that specific inflammatory components (cells, cytokines and chemokines) are central promoters of regeneration.…”
Section: Perspective On the Effect Of The Immune System In The Evolution Of Regenerative Capacitiesmentioning
confidence: 99%